Nuclear Assessment of Right Ventricle. (19th September 2014) - Gargiulo, Paola; Cuocolo, Alberto; Dellegrottaglie, Santo; Prastaro, Maria; Savarese, Gianluigi; Assante, Roberta; Zampella, Emilia; Paolillo, Stefania; Scala, Oriana; Ruggiero, Donatella; Marsico, Fabio; Perrone Filardi, Pasquale
Abstract : For many years, the right ventricle (RV) has been considered a passive chamber with a relatively insignificant role in the overall functionality of the heart. More recently, the role of performance of RV in the clinical presentation and long‐term prognosis of multiple pathological states, such as congenital heart diseases, chronic heart failure, pulmonary hypertension, and chronic obstructive pulmonary disease. Despite echocardiography and cardiac magnetic resonance are the 2 most commonly used imaging techniques for noninvasive assessment of RV, nuclear imaging provides new opportunities for comprehensive evaluation of RV from a single study, because it can assess right ventricular perfusion and metabolism as well as morphology and ejection fraction. In this review, we summarize the application of radionuclide techniques (nuclear cardiology) for evaluation of the RV, focusing on its emerging role in the assessment of right ventricular perfusion and metabolism.